Avaliação da técnica de coleta spot de urina e síntese microbiana ruminal através da creatinina, em ovinos em crescimento - Ferreira, Francisca Debora da Silva (2023)
The aim of this study is to establish a protocol to validate the spot collection methodology to estimate nitrogen excretion, microbial protein synthesis, as well as the factors that influence the excretion of creatinine and purine derivatives in growing sheep. Fifteen Santa Inês sheep, male, intact, with body weight (BW) ranging from 14.0 to 30.9 kg ± 5.32 were used. The animals were fed with Tifton 85 grass hay and concentrate, composed of ground corn, soybean meal and mineral mixture, in the proportion 60:40, respectively. Analyzes of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDFcp), non-fiber carbohydrates (NFC) and total digestible nutrients (TDN) were performed to determine the intake, digestibility, nitrogen balance, microbial crude protein (MCP), and microbial efficiency. Total urine collections (24 hours) were performed during the period of five consecutive days and punctual collections (spot), which were obtained during two consecutive days: 00:00, 04:00, 08:00, 12 :00, 4:00 pm and 8:00 pm. Creatinine, uric acid and N-urea. Purine Derivatives (DP) and Ratios: Purine Derivatives:Creatinine (DP:C) and Urea:Creatinine (U:C). The correlation of DMI and nutrients with BW (r²= 0.87) was verified. Creatinine (mg/day) had a positive linear correlation with BW (Y=0.0362x+10.271), and with cold carcass weight (CCW) (Y=0.0146x + 8.3627) with the coefficients of r² =0.55 and r²=0.61, respectively. The excretions of DP mmol/d, coefficients r²=0.55 and r²=0.53 were verified in relation to BW (Y = 2.1485x + 2.6913) CCW (Y= 0.8309x + 5.6455). In spot urine samples, results were obtained in confidence intervals (P < 0.01), in collections carried out at 0, 4 and 12 hours for creatinine excretion (mg/L), 12 and 20 hours, for the DP:C ratio (mg/L) and 8 and 16 hours for the U:C (mg/L). Creatinine showed a moderate correlation (0.56) with BW and CCW (0.61). Creatinine excretion ranged from 11.03 to 23.24 (mg/Kg). The period of four hours after feeding indicated to perform spot urine collections to estimate microbial synthesis in growing sheep.